Mediators of the effect of the psycho-educational intervention on the psychological well-being of caregiving daughters and daughter in-laws of stroke survivors - Gholamzadeh, Sakineh; Tengku Abdul Hamid, Tengku Aizan; Basri, Hamidon; Ibrahim, Rahimah; Sharif, Farkhondeh (Sciedu Press, 2013)
Background: The objective of this study was to determine whether the randomly assigned intervention is associated with a change in the mediators including threat appraisal, coping behaviors, confidence in knowledge, and preparedness which is in turn accompanied by changes in the caregivers’ psychological well-being. Methods: A total of 96 caregiving daughters and daughter in-laws of stroke survivors participated in the study in which 49 cases were randomly assigned to the intervention and 47 to the control group. Data was collected before, immediately after and 12 weeks following interventions. Results: The results of mixed ANOVA revealed a statistically significant difference in psychological well-being score between intervention and control groups. Our findings from the multiple mediator analyses supported the mediating effect for only two of the five hypothesized mediators. The intervention affected psychological well-being indirectly through changes in threat appraisal and perceived preparedness. Multiple mediator models accounted for 34.3% of the variance in the psychological well-being change. Conclusion: The results of this study show the importance of mediators’ evaluation in interventional studies of stroke survivor caregivers.